WHIRLY1 functions in the nucleus to regulate barley leaf development and associated metabolite profiles. Issue 5 (4th March 2022) - Karpinska, Barbara; Razak, Nurhayati; James, Euan K.; Morris, Jenny A.; Verrall, Susan R.; Hedley, Peter E.; Hancock, Robert D.; Foyer, Christine H.
Abstract : The WHIRLY (WHY) DNA/RNA binding proteins fulfil multiple but poorly characterised functions in leaf development. Here, we show that WHY1 transcript levels were highest in the bases of 7-day old barley leaves. Immunogold labelling revealed that the WHY1 protein was more abundant in the nuclei than the proplastids of the leaf bases. To identify transcripts associated with leaf development we conducted hierarchical clustering of differentially abundant transcripts along the developmental gradient of wild-type leaves. Similarly, metabolite profiling was employed to identify metabolites exhibiting a developmental gradient. A comparative analysis of transcripts and metabolites in barley lines (W1–1 and W1–7) lacking WHY1, which show delayed greening compared with the wild type revealed that the transcript profile of leaf development was largely unchanged in W1–1 and W1–7 leaves. However, there were differences in levels of several transcripts encoding transcription factors associated with chloroplast development. These include a barley homologue of the Arabidopsis GATA transcription factor that regulates stomatal development, greening and chloroplast development, NAC1; two transcripts with similarity to Arabidopsis GLK1 and two transcripts encoding ARF transcriptions factors with functions in leaf morphogenesis and development. Chloroplast proteins were less abundant in the W1–1 and W1–7 leaves than the wild type. The levels of tricarboxylic acid cycle metabolites and GABA were significantly lower in WHY1 knockdown leaves than the wild type. This study provides evidence that WHY1 is localised in the nuclei of leaf bases, contributing the regulation of nuclear-encoded transcripts that regulate chloroplast development.